The impact of institutions on Regional unemployment disparities - Floro Ernesto Caroleo; Gianluigi Coppola (European Regional Science Association (ERSA), 2005)
In this paper We explain the regional unemployment disparities in Europe using a set of institutional indicators trough an Econometric Panel data analysis. In particularly the aim of t he paper is to evaluate if the regional disparities in the unemployment rates are due to different economy structure and/or to institutional rigidity of national/regional labour markets. A Regional data set has been constructed in order to estimate the relationship between the unemployment rate, institutional factors, and some other variables that measure the regional productive structure(Amendola, Caroleo, Coppola, 2003).
Keywords: 330